2017
DOI: 10.1002/jmv.24773
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's sarcoma‐associated herpesvirus (KSHV)‐encoded microRNAs promote matrix metalloproteinases (MMPs) expression and pro‐angiogenic cytokine secretion in endothelial cells

Abstract: The human oncogenic virus Kaposi's sarcoma-associated herpesvirus (KSHV) is linked to Kaposi's sarcoma (KS), a tumor of endothelial cells characterized by angiogenesis and invasiveness. KSHV genome encodes 25 mature microRNAs (miRNAs), but their roles in KSHV-induced tumor dissemination and angiogenesis are not fully understood. In this study, we constructed the sensor reporters of KSHV miRNAs and used a luciferase reporter assay to demonstrate the function of the mimics of KSHV miRNAs. Then, we examined the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Numerous KSHV miRNAs induce inflammation by activating the NF-κB pathway [112,242]. Ectopic expression of the miRNA cluster in endothelial cells induces the expression of pro-inflammatory and proangiogenic cytokines MMP1, MMP13, and VEGFA [286]. VEGF is important for the recruitment of stem cells and macrophages at the site of infection, and therefore participates in the inflammatory microenvironment of KS tumors [287].…”
Section: Latent Viral Factors Involved In Inflammationmentioning
confidence: 99%
“…Numerous KSHV miRNAs induce inflammation by activating the NF-κB pathway [112,242]. Ectopic expression of the miRNA cluster in endothelial cells induces the expression of pro-inflammatory and proangiogenic cytokines MMP1, MMP13, and VEGFA [286]. VEGF is important for the recruitment of stem cells and macrophages at the site of infection, and therefore participates in the inflammatory microenvironment of KS tumors [287].…”
Section: Latent Viral Factors Involved In Inflammationmentioning
confidence: 99%
“…Along with in-depth analyses of microRNAs (miRNAs or miRs), certain studies have suggested that upregulation of miRNAs can inhibit MMP13 expression (9,10). miRNAs are associated with regulating differentiation and maturation of immune cells, including T cells and B cells (11); osteogenic differentiation of stromal cells (12); expression of inflammatory cytokines and immune responses (13); host-virus interactions (14); and the sugar metabolism in the body (15).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, KSHV vIL-6 induced VEGFA expression, which promoted vascular permeability [64] while K1 promoted the expression and release of VEGFA [65]. Furthermore, KSHV miRNAs also increased the expression of VEGFA, as well as the secretion of VEGFA protein [66,67]. It is well known that activation of JNK signaling induces VEGFA production [33,68].…”
Section: Plos Pathogensmentioning
confidence: 99%